The role of PTPN11 in MAPK/ERK signaling pathway and its impact on the occurrence and development of glioma - Zhang, Xiuming (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The protein tyrosine phosphatase, PTPN11, exerts a crucial inhibitory influence on the MAPK/ERK signaling cascade. This research endeavored to unravel the involvement of PTPN11 in the initiation and progression of glioma, as well as its underlying molecular interactions. To achieve this, Western blotting was employed to observe alterations in ERK phosphorylation upon PTPN11 depletion or amplification. Furthermore, immunoprecipitation coupled with mass spectrometry was utilized to pinpoint the targets of PTPN11’s enzymatic activity. The outcomes demonstrated that the absence of PTPN11 significantly enhanced ERK phosphorylation, whereas an excess of the protein had the converse effect. In-depth explorations into the molecular mechanisms highlighted that PTPN11’s inhibitory action is chiefly executed through the deactivation of Ras proteins by dephosphorylation. These revelations accentuate the critical part played by PTPN11 within the MAPK/ERK pathway in relation to glioma development and offer insights that could lead to innovative treatments for this disease.